Enhancement of dispersion of nano-catalysts for catalytic hydrogenation of cinnamaldehyde by a rotating packed bed. (31st August 2021) - Dong, Kun; Ma, Xiaoke; Chu, Guang-Wen; Zou, Hai-Kui; Luo, Yong; Sun, Bao-Chang
Highlights: A rotating packed bed (RPB) was adopted for the dispersion of nano-Ni. A correlation to predict the average particles size (D[3, 2]) was established. The catalytic performance for RPB was studied by the hydrogenation of cinnamaldehyde. The reaction rate of CAL obtained in RPB were about twice that in the STR. Abstract: This work presents the dispersion of Ni nanoparticles into the ethanol solution without surfactant in a rotating packed bed (RPB). The effects of different operating parameters on the particles size distribution (PSD) of Ni nanoparticles in the solution were investigated. Furthermore, the influence of dispersion process on the catalytic performance was investigated by the catalytic hydrogenation of cinnamaldehyde using Ni-Pt nanoparticles as catalyst. Also, a correlation to predict the average particles size ( D [3, 2]) was established, and the predicted D [3, 2] fitted well to the experimental data with a deviation within 10%. The experimental results indicated that RPB could significantly intensify the dispersion of Ni nanoparticles in the solution, which is beneficial for the nano-catalysis reaction process. Catalytic results showed that the reaction rate of CAL obtained in RPB were about twice that in the stirring tank reactor at H2 pressure of 2 MPa.